2018
DOI: 10.1108/imefm-05-2017-0134
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing behaviour to participate in Islamic microfinance

Abstract: Purpose The purpose of this paper is to empirically examine the factors that affect Muslim customers’ participation in using Baitul Maal wat Tamwil (BMT). The decomposed theory of planned behaviour (DTPB) was used as the research framework. Design/methodology/approach The paper uses primary data collected by self-administered questionnaires involving a sample of 405 respondents from selected BMTs in five different regencies in East Java. Structural equation modelling was used in the analysis. Findings This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
74
3
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(93 citation statements)
references
References 34 publications
8
74
3
8
Order By: Relevance
“…In another study Schmidt, N. (2010) proposed that perceptions and ability to control investment in mutual funds have a significant positive impact on private investor general willingness to purchase mutual funds. Moreover, Maulana, Razak & Adeyemi (2018) suggested that positive beliefs about perceived behavioral control have a positive significant impact on participating in Islamic microfinance. In the view of the above discussion, it can be assumed that perceived control over investment will positively and significantly influence investment in Islamic sukuk.…”
Section: Perceived Control Over Investment and Investment In Islamic mentioning
confidence: 99%
“…In another study Schmidt, N. (2010) proposed that perceptions and ability to control investment in mutual funds have a significant positive impact on private investor general willingness to purchase mutual funds. Moreover, Maulana, Razak & Adeyemi (2018) suggested that positive beliefs about perceived behavioral control have a positive significant impact on participating in Islamic microfinance. In the view of the above discussion, it can be assumed that perceived control over investment will positively and significantly influence investment in Islamic sukuk.…”
Section: Perceived Control Over Investment and Investment In Islamic mentioning
confidence: 99%
“…Penelitian ini menunjukkan nilai eigenvalues yang memenuhi persyaratan adalah Component 1 (6,504) maka menjadi faktor 1 dan mampu menjelaskan 34,230% varian, Component 2 (1,769) menjadi faktor 2 dan mampu menjelaskan 9,309% varian, Component 3 (1,486) menjadi faktor 3 dan mampu menjelaskan 7,822% varian, Component 4 (1,242) menjadi faktor 4 dan mampu menjelaskan 6,538% varian, Component 5 (1,114) menjadi faktor 5 dan mampu menjelaskan 5,866% varian. Nilai total component 6,7,8,9,10,11,12,13,14,15,16,17,18,19 Faktor terbentuk yang berisikan variabel-variabel yang diteliti tersebut kemudian dilakukan penamaan faktor berdasarkan karakteristik yang sesuai dengan variabel-variabel yang dirangkum di dalamnya. Faktor 1 memiliki anggota yang terdiri atas variabel Eksploitasi Jabatan, Nilai Manfaat, Peningkatan Kinerja, Pemanfaatan Teknologi, Disintegrasi Informasi, Inovasi Serta Ketidaknyamanan Layanan.…”
Section: Metode Penelitianunclassified
“…Jika dua hal di atas (baca: pelayanan dan fasilitas) diabaikan, maka akan menimbulkan disloyalitas. 10 12 Disebutkan pula dalam penelitian Zikiene dan Lina, faktor yang mendukung beralihnya tingkah laku (baca: loyal menjadi disloyal) yaitu berkaitan dengan harga, ketidaknyamanan, kegagalan layanan inti, kualitas tidak memuaskan, kegagalan pertemuan layanan dan pencarian varietas, berganti tempat tinggal pelanggan serta adanya nilai baru. Sehingga faktor tersebut juga menjadi perhatian kaitannya dengan perubahan tingkah laku nasabah menjadi loyal atau disloyal.…”
unclassified
See 1 more Smart Citation
“…Technological security does not depend on this device. Instead the responsibility rests with users, service providers and financial institutions (banks), (Maulana, et.al., 2018) 8 , revealing that among the three main beliefs, only behavioral control on BMT was found to have a positive and significant impact on client participation against BMT. From the description above it can be seen that the previous researchers examined by looking at the relationship between several variables.…”
Section: Introductionmentioning
confidence: 99%